Gambaran Pengelolaan Menyusui Tidak Efektif pada Ibu Post Partum Spontan di Puskesmas Guntur 2 Kabupaten Demak: Description of Ineffective Breastfeeding Management for Spontaneous Postpartum Mothers at the Guntur 2 Health Center, Demak Regency - Resa Dian Sulistyani; Siti Haryani (Journal of Holistics and Health Sciences (JHHS), 2023)
Postpartum maternal health problems still require attention in handling. One of them is ineffective breastfeeding. Ineffective breastfeeding is a condition where the mother and baby experience dissatisfaction or difficulty with breastfeeding. This study aims to provide an overview of ineffective management of breastfeeding in spontaneous post partum mothers. The type of research used in this compilation uses a descriptive method with a case study design with an assisted care approach including assessment, formulating a diagnosis of involvement, development intervention, implementation of implementation, and evaluation. The research subjects were post partum mothers who experienced ineffective breastfeeding problems. Breastfeeding care is not effective for 3 x 24 hours. interventions made to address ineffective breastfeeding problems include breastfeeding education and lactation counseling by prohibiting breast care using breast care techniques and oxytocin massage. Based on the actions taken, it was found that patient data said that the milk had come out. The results of the analysis can be concluded that ineffective breastfeeding can be overcome. It is hoped that patients can carry out humanitarian actions that have been taught about breast care properly and correctly to anticipate problems in post partum mothers' breasts.   ABSTRAK Masalah kesehatan ibu post partum masih membutuhkan perhatian dalam penangannannya. Salah satunya adalah menyusui tidak efektif.  Menyusui tidak efektif merupakan suatu kondisi dimana ibu dan bayi mengalami ketidakpuasan atau kesulitan pada saat menyusui. Penelitian ini bertujuan untuk memberikan gambaran tentang pengelolaan menyusui tidak efektif pada ibu post partum spontan. Jenis penelitian yang digunakan dalam penyusunan ini menggunakan metode deskriptif dengan rancangan studi kasus dengan pendekatan asuhan keperawatan meliputi pengkajian, merumuskan diagnosa keperawatan, intervensi keperawatan, implementasi keperawatan, dan evaluasi. Subyek penelitian adalah ibu post partum yang mengalami masalah menyusi tidak efektif. Asuhan keperawatan menyusui tidak efektif dilakukan selama 3 x 24 jam . Intervensi keperawatan yang dilakukan untuk mengatasi masalah menyusui tidak efektif antara lain edukasi menyusui dan konseling laktasi dengan mengajarkan perawatan payudara menggunakan teknik breast care dan pijat oksitosin. Berdasarkan tindakan keperawatan yang dilakukan, didapatkan data pasien mengatakan ASI sudah keluar. Hasil analisis dapat disimpulkan bahwa menyusui tidak efektif dapat teratasi. Bagi pasien diharapkan dapat melakukan tindakan keperawatan yang sudah diajarkan tentang perawatan payudara dengan tepat dan benar untuk mengantisipasi permasalahan pada payudara ibu post partum.